Oil and Gas Futures and Options Market (Rudarsko-geološko-naftni zbornik, 2017)
Energy mineral resources markets are represented by complex supply and demand ratios which are depending on different factors such as technical (transport) and geopolitical. The main specific of energy markets is represented by an uneven geographic distribution of hydrocarbon reserves and exploration on one hand and energy consumption on the other. World oil markets, although geographically localized, because of specific market trade, represent unique global market with decreasing price difference. Price differences are result of development of a transport possibilities of oil supply. Development of transport routes of natural gas and increasing number of liquefied natural gas terminals in the world give pressure to natural gas market and its integration into global gas market. Integration of regional gas markets into a common European gas market is main energy policy of EU concerning natural gas. On the other hand, there are still significant price differences on some markets (e.g. United States of America - South East Asia). Development of global energy markets is enabled by development of a futures and options contracts of an energy trade which have replaced bilateral contract deals between producers and consumers. Futures contracts are standardized contracts traded on exchanges. Buyer agrees to buy certain quantity of stock for an agreed upon price and with some future delivery date. Option is a contract which gives a buyer the option of the right to buy (or sell, depending on the option) an asset at predetermined price and at a later date. Stocks price risk can be managed with the purchase and selling futures and options contracts. This paper deals with futures and options energy markets and their market strategies.